2011
DOI: 10.1016/j.nano.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of anti-angiogenic property of gold nanoparticles: role of nanoparticle size and surface charge

Abstract: Discovering therapeutic inorganic nanoparticles is evolving as an important area of research in the emerging field of nanomedicine. Recently, we reported the anti-angiogenic property of gold nanoparticles (GNPs): it inhibits the function of pro-angiogenic heparin-binding growth factors (HB-GFs) such as vascular endothelial growth factor 165 (VEGF165), basic fibroblast growth factor (bFGF), etc. However, the mechanism through which GNP imparts such an effect remains to be investigated. Using GNPs of different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
183
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(189 citation statements)
references
References 44 publications
5
183
0
1
Order By: Relevance
“…Next we sought to determine the effect of these AuNPs on the proliferation of three different ovarian cancer cell lines-A2780, OVCAR5, and SKOV3-ip cells-and compare them with normal ovarian surface epithelial (OSE) (18) cells. Our findings demonstrated that both size and concentration of AuNPs play a pivotal role in inhibiting the proliferation of ovarian cancer cells (as determined by 3 [H]-Thymidine incorporation), in a timedependent manner ( Fig. 1 and Fig.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Next we sought to determine the effect of these AuNPs on the proliferation of three different ovarian cancer cell lines-A2780, OVCAR5, and SKOV3-ip cells-and compare them with normal ovarian surface epithelial (OSE) (18) cells. Our findings demonstrated that both size and concentration of AuNPs play a pivotal role in inhibiting the proliferation of ovarian cancer cells (as determined by 3 [H]-Thymidine incorporation), in a timedependent manner ( Fig. 1 and Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Furthermore, activation of this pathway is also known to induce EMT in cancer cells (19). Since AuNPs disrupt HB-GF-mediated signaling (3,20,21), we wanted to determine whether inhibition of AuNP-mediated proliferation could be due to an inhibition of MAPK activation in cancer cells. Our results revealed a substantial, concentration-dependent inhibition of p42/44 phosphorylation in ovarian cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations